The Women’s Liberation Movement. Impacts and Outcomes - Schulz, Kristina (New York: Berghahn Books, 2017)
For over half a century, the countless organizations and initiatives that comprise the Women’s Liberation movement have helped to reshape many aspects of Western societies, from public institutions and cultural production to body politics and subsequent activist movements. This collection represents the first systematic investigation of WLM’s cumulative impacts and achievements within the West. Here, specialists on movements in Europe systematically investigate outcomes in different countries in the light of a reflective social movement theory, comparing them both implicitly and explicitly to developments in other parts of the world.
Keywords: Women's Liberation Movement; Feminism; Equality; Abortion; Comparaison; Social Movements